Primary Culture of Alveolar Epithelial Type Ⅱ Cells and Its Bionomic Study - 史雪梅 张惠兰 熊盛道 甄国华 熊维宁 张珍徉 徐永健 胡琼洁 赵建平 倪望 (Journal of Huazhong University of Science and Technology. Medical sciences, 2007)
To establish a better method of primary culture for alveolar epithelial type Ⅱ cells （AEC Ⅱ ） and to study its bionomics, alveolar epithelial type Ⅱ cells were isolated by digestion with trypsin and collagenase, which were then purified by plated into culture flask coated with rat immunoglobulin （i The purified AEC Ⅱ were identified by alkaline phosphatase staining, electron mi- croscopy, immunocytochemical staining of pulmonary surfactant protein A （SPA）. The SPA expression and transfection characteristics were compared with those of A549 cell line. The results showed that AEC Ⅱ could be isolated by digestion with trysin and collagenase and purified by adhesive purification by using IgG, with a yield of about 2-3 × 10^7, and a purity of about 75%-84 %. Cells could be quickly identified with AKP staining. AEC Ⅱ were different from A549 cell line in terms of SPA expression and transfection characteristics. It is concluded that adhesive purification with IgG can improve the purity of AEC Ⅱ, and AKP staining is simple in cell identification. AEC Ⅱ can not be completely replaced by A549 cells in some studies because the differences between them, such as SPA expression.